WEIGHT-MEASURING DEVICES OF RUP “BMZ”. THE MAIN PROBLEMS OF PROVIDING OF THE REQUIRED ACCURACY AT DETERMINATION OF MASS AND WAYS OF THEIR SOLVING - I. V. Bujanova; E. V. Borisenko (Литьë и металлургия)
The main problems of providing of the required accuracy at determination of mass and ways of their solution at RUP '‘BMZ” are examined.